The Influence of Liturgical Music and Song on Congregation of Saint Cornelius Madiun Church at 2019 - Rif’at Husnul Ma’afi; Dzakiyyah Fauziyah Rif’at (Journal of Comparative Study of Religions (JCSR), 2021)
Music has an important role in the Catholic act of worship. Liturgy, as the mainact of worship, has always been using music and song to increase the number of its.Saint Cornelius Madiun Church as one of the Surabaya diocese has a big developmentin accord to the number of the congregation since its establishment. This parish hasthree thousand congregations and still increasing annually. One of these factors iscaused by the unique music and song served by the ministry of the church. Thisresearch is field research and employed the phenomenological approach to analyzethe data. The result is that the liturgical music and song which are played in SaintCornelius Madiun Church are in accord with what has been determined by the CouncilVatican 2, namely Sacrosanctum Concilium about liturgical Music. Both are music as apart of the liturgy, and music as accompaniment music during liturgy. The music andthe song of the liturgy give big influence in creating a sense of solem, sacred, humilityand delighted in living up to the liturgy of the mass because music has a variety oftempo, rhythm, and a style adapted to the liturgical activities. Besides, the lyrics ofthe song become the main factor to touch the heart of the congregation and expressesthe intention that wants to be conveyed by the performed music.